High-latitude snowfall as a sensitive indicator of climate warming: A case study of Heilongjiang Province, China - Lijuan Zhang (Elsevier, 2021)
While global distribution and dynamics of snow extent and snow depth have been intensely studied, the response of snowfall events to global warming is complex and remains unclear in current literature. This study explores historical snowfall records since the 1960s at 62 meteorological stations in Heilongjiang Province, and examines the snowfall responses in this most northerly high-latitude snow zone of China. Results confirm a significant increase of annual average temperature with a turn-over year in 1987, representing a shift of a cooler to warmer climate. Our study reports five most sensitive snowfall indicators of the warmer climate: snow intensity, snow phenology (first snow day, last snow day, snow season) and light snow days, all revealing significant trends and strong relationships with annual temperature. Their turn-over years responded rapidly after 1987. Overall, the study area has experienced significantly delayed first snow, advanced last snow and a shorter snow season; snowfall intensity has become stronger accompanying the decreased light snow days. Total snow amount and extreme snow events (blizzard and heavy snow) are found not sensitive indicators of a warmer climate; other influences such as atmospheric circulation may have played a role in their significant increase in the study period. Light snow is the predominant snow class of the study area. Its decreased snow days may negatively impact snow water availability of this important agricultural region of China.